Web-Based CRM pada Mr.Syafii Bakery Terhadap Peningkatan Pelayanan dan Retensi Pelanggan - Wiwin Dila; Novica Irawati; Maulana Dwi Sena (Jurnal Algoritma, 2026)
Advances in information technology have encouraged food business operators to adopt digital systems to improve customer service and retention. However, Mr. Syafii Bakery still faces challenges in managing customer data and transactions, which are currently handled manually. This study aims to develop a web-based Customer Relationship Management (CRM) system to improve service and customer retention. The method used is systems engineering with the System Development Life Cycle (SDLC) Waterfall approach. System evaluation was conducted using Black Box Testing and the System Usability Scale (SUS). The results show that the system functions well and achieved a SUS score of 78 (good category). Additionally, customer retention increased from 37.5% to 52.3%, or by approximately 14.8%, following the system’s implementation. The contribution of this research lies in the development of an integrated CRM system that combines customer data management, interactions, and promotional strategies into a single platform to support improved service and customer retention for culinary SMEs.